2015
DOI: 10.1088/0264-9381/32/19/195017
|View full text |Cite
|
Sign up to set email alerts
|

Einstein–Maxwell Dirichlet walls, negative kinetic energies, and the adiabatic approximation for extreme black holes

Abstract: The gravitational Dirichlet problem -in which the induced metric is fixed on boundaries at finite distance from the bulk -is related to simple notions of UV cutoffs in gauge/gravity duality and appears in discussions relating the low-energy behavior of gravity to fluid dynamics. We study the Einstein-Maxwell version of this problem, in which the induced Maxwell potential on the wall is also fixed. For flat walls in otherwiseasymptotically-flat spacetimes, we identify a moduli space of Majumdar-Papapetrou-like … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…The structure is similar to that of a two-sided wormhole where the ADM Energy is separately conserved in each asymptotic region. On (perhaps AdS or dS) Schwarschild, extending the computations of [39] to λ = 0 and using the sign appropriate to being outside the wall gives In a recent article [14], we used the small velocity approximation to study the motion of a spherical extreme electrically-charged black hole in an asymptotically flat spacetime that contains a flat Dirichlet wall. Our results suggested that system to be unstable due to the appearance of negative kinetic energies for black holes near the wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure is similar to that of a two-sided wormhole where the ADM Energy is separately conserved in each asymptotic region. On (perhaps AdS or dS) Schwarschild, extending the computations of [39] to λ = 0 and using the sign appropriate to being outside the wall gives In a recent article [14], we used the small velocity approximation to study the motion of a spherical extreme electrically-charged black hole in an asymptotically flat spacetime that contains a flat Dirichlet wall. Our results suggested that system to be unstable due to the appearance of negative kinetic energies for black holes near the wall.…”
Section: Discussionmentioning
confidence: 99%
“…In the particular case where the intrinsic metric is fixed, we call this surface a "Dirichlet wall." With such motivations in mind, we recently considered the problem of a black hole moving through a spacetime with a Dirichlet wall [14]. In order to make the problem analytically tractable, we considered the extreme multi-black-hole solutions of [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Dirichlet boundary conditions at finite bulk radius have been studied at classical level in[50][51][52][53].…”
mentioning
confidence: 99%
“…Since there is no dynamics at leading order, the relevant equations are the constraints 3. See[25] for a critical discussion of this approximation.…”
mentioning
confidence: 99%